Farmers' perspective on the implementation of the affordable inputs programme: Insights from nationally representative household and community surveys - Ragasa, Catherine; Carrillo, Lucia; Balakasi, Kelvin (International Food Policy Research Institute, 2022)
This note provides an assessment of the first year of implementation of the Affordable Inputs Programme (AIP) from the perspective of rural households and communities in Malawi. The data come from a nationally representative panel survey of 2,449 rural households in 299 communities. At the household level, users of inorganic fertilizer, the amount applied per farmer, and productivity and production all increased in the 2020/21 cropping season compared to the 2015/16 and 2017/18 seasons. Almost all sampled communities reported more positive experiences with AIP than with the previous Farm Input Subsidy Programme (FISP), mainly because of the expanded coverage and greater number of beneficiaries. However, farmers reported major challenges in the computerized system (or network) for verifying beneficiaries, limited number of selling points, and limited and late supply of inputs, causing congestion and different forms of corruption and harassment in the selling points. The network, number of selling depots, procurement processes, input-provider selection processes, and governance must improve for more farming households to realize benefits from AIP. Further, AIP must be accompanied in the long term by better soil management practices.